Activated hepatic stellate cell-derived small extracellular vesicles facilitate M2 macrophage polarization and hepatoma progression via miR-27a-3p - Sun, Yufeng; He, Xiaoqian; Han, Jiayi; Yin, Wenxuan; Wang, Haichen; Li, Jing; Liu, Weiqi; Kuai, Xingwang; Lv, Jiaying; Ji, Juling (Frontiers in Immunology, 2024)
The progression of hepatoma is heavily influenced by the microenvironment. Tumor-associated macrophages (TAMs) are considered to play a critical role in the tumor microenvironment (TME) and increase the aggressiveness of hepatoma. The activation of hepatic stellate cells (HSCs) is involved in hepatoma progression, and accumulating evidence demonstrates a change in microRNA (miRNA) expression during HSC activation. Therefore, the potential roles of HSCs-related miRNAs in macrophage differentiation and hepatoma progression deserve to be explored. The present study aimed to investigate the effects of miRNAs carried by small extracellular vesicles (sEVs) released by activated HSCs on hepatoma progression. The results indicated that miR-27a-3p was significantly upregulated in cells and corresponding sEVs during the activation of primary rat HSCs and human HSC line-LX2 cells. Furthermore, miR-27a-3p contributed to the proliferation and migration of hepatoma cells and promoted M2 polarization of macrophage. HSC-sEVs overexpressing miR-27a-3p can directly facilitate tumor progression and modulate macrophage polarization, indirectly contributing to hepatoma progression. Finally, Sprouty2 (SPRY2) was verified to be the target gene of miR-27a-3p. In conclusion, activated HSC-derived sEVs with high levels of miR-27a-3p might induce M2 macrophage polarization and promote hepatoma progression, providing new insights into the mechanism of hepatoma progression.